“TOING DAN TITONG”: REFLEKSI KONTEKSTUAL PENDIDIKAN BERBASIS BUDAYA - Selatang, Fabianus (STP St. Bonaventura Medan, 2018)
Reflection is the basis of the distinction between the real and the ideal. Reflection shows that education is an integrated, dynamic system that leads to certain goals. That is the ideal of education. However, the reality on the ground certainly still leaves many problems. Indonesian-NTT educational migration now predominantly tends towards Java, specifically Malang. Every year, both state and private campuses are always flooded with students from NTT, especially Manggarai. However, the problem is that the output (graduates) and the availability of job opportunities in Manggarai are not comparable. The method used in this paper is descriptive-qualitative. The approach is cultural. In the human mind, culture that appears materially and specifically is then universalized conceptually. Therefore, through this article, the author wants to explore these universal values in the expressions toing and titong. Toing and titong are historical products and historical facts that teach very basic educational values for the Manggarai people.